Physicochemical properties of rambutan (Nephelium lappaceum L.) seed during natural fermentation of the whole peeled fruit - Chai, K. F.; Adzahan, N. M.; Karim, R.; Rukayadi, Y.; Ghazali, H. M. (IFRJ, Faculty of Food Science & Technology, UPM, 2020)
A novel way to reduce rambutan wastage is to ferment the fruit and valorise the seed post-fermentation into other food products and ingredients. Hence, the objective of this study was to investigate the physicochemical properties of rambutan seed during solid-state fermentation of the fruit. Peeled rambutan fruits were subjected to natural fermentation for ten days at 30°C. The environmental temperature, relative humidity, internal and external temperatures of the fermentation mass were measured daily. After ten days of fermentation, the seeds had higher cut test score (867.5), fermentation index (1.527), and a* value (8.20 for non-dried seeds and 9.93 for dried seeds), and lower L* (51.90 for non-dried seeds and 49.22 for dried seeds) and b* (30.52 for non-dried seeds and 30.12 for dried seeds) values; as compared to the non-fermented seeds (cut test score, 0.0; fermentation index, 0.856; L*, a*, and b* values, 64.52, 2.25, and 42.07 for non-dried seeds, respectively, and 61.03, 3.23 and 36.70 for dried seeds, respectively). During this time, pH, total soluble solids, fructose, glucose, sucrose, citric acid, and tartaric acid contents of the seeds decreased by 46, 44, 59, 61, 100, 85, and 100%, respectively, while the titratable acidity, lactic acid, acetic acid, and ascorbic acid contents of the seeds increased by 5.5, 7.8, 6.0, and 2.2-fold, respectively. Results showed that eight days of fermentation are adequate to produce well-fermented rambutan seeds that could be further processed into a cocoa powder-like product by roasting the fermented fruits in a manner similar to that of cocoa bean roasting.